Effect of Leadership, Personality and Job Satisfaction On Job Performance of Diplomat - Hadiningrat, June Kuncoro; R. Luddin, Muchlis; Suyatno, Thomas (International Journal of Scientific Research and Management (IJSRM), 2018)
This research aims to study the effect of leadership, personality and job satisfaction on diplomat performance in the Ministry of Foreign Affairs of the Republic of Indonesia. The research methodology was a survey with path analysis applied in testing hypothesis. It was conducted among 158 diplomats selected  by simple random sampling from 657 young diplomat population. Data analysis and interpretation indicate that (1) leadership has a positive direct effect on job performance of diplomat/diplomat performance, (2) personality has a positive direct effect on diplomat performance, (3) job satisfaction has a positive direct effect on diplomat performance, (4) leadership has a positive direct effect on job satisfaction, (5) personality has a positive direct effect on job satisfaction.